Morphological and Anatomical Identification of Rhizoctonia Mycorrhizal from Five Dendrobium Sp. - R Soelistijono; Syalaysa Imani Fatihah (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2026)
Orchids are one of the plants that do not have food reserves (endosperm), so they require mycorrhizal fungi (Orchid mycorrhizal fungi / OMF) to help absorb nutrients and support seed germination. A more detailed understanding of the mycorrhizal character of each orchid species is very necessary because each orchid has a different OMF to support more optimal cultivation. This study aims to determine and identify the types of OMF morphologically and anatomically belonging to the Rhizoctonia mycorrhizal group that are able to associate with five species of Dendrobium sp. orchids, namely Dendrobium spectabile, Dendrobium lineale, Dendrobium aphyllum, Dendrobium discolor, and Dendrobium fimbriatum. The method used is the observation method by taking 150 OMF samples. Based on the results of cell nucleus observations, isolates from D. aphyllum have the highest percentage of binucleate cells (80%), so they are considered the most stable and have strong potential as functional mycorrhizae. In contrast, D. discolor had the lowest binucleate value (44%), indicating a weaker symbiotic ability compared to other isolates. Overall, this study demonstrates that host orchid species influence the characteristics of Rhizoctonia mycorrhizal. This information can be used as a basis for developing orchid cultivation technology and further research through molecular analysis.